Spectrum and morphology of the very-high-energy source HAWC J2019+368 - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Arunbabu, K. P.; Rojas, D. Avila; Solares, H. A.Ayala; Baghmanyan, V.; Belmont-Moreno, E.; Brisbois, C.; Caballero-Mora, K. S.; Capistrán, T.; et al. (Astrophysical Journal, 2021)
The MGRO J2019+37 region is one of the brightest sources in the sky at TeV energies. It was detected in the second HAWC catalog as 2HWC J2019+367 and here we present a detailed study of this region using data from HAWC. This analysis resolves the region into two sources: HAWC J2019+368 and HAWC J2016+371. We associate HAWC J2016+371 with the evolved supernova remnant CTB 87, although its low significance in this analysis prevents a detailed study at this time. An investigation of the morphology (including possible energy-dependent morphology) and spectrum for HAWC J2019+368 is the focus of this work. We associate HAWC J2019+368 with PSR J2021+3651 and its X-ray pulsar wind nebula, the Dragonfly nebula. Modeling the spectrum measured by HAWC and Suzaku reveals a ∼7 kyr pulsar and nebula system producing the observed emission at X-ray and γ-ray energies.
CRIS-Team Scopus Importer:2021-05-21